Cochrane Database of Systematic Reviews 2001
DOI: 10.1002/14651858.cd002817
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy versus placebo or no intervention in Parkinson's disease

Abstract: BackgroundDespite medical therapies and surgical interventions for Parkinson's disease (PD), patients develop progressive disability. The role of physiotherapy aims to maximise functional ability and minimise secondary complications through movement rehabilitation within a context of education and support for the whole person. The overall aim is to optimise independence, safety and well-being, thereby enhancing quality of life. ObjectivesTo assess the effectiveness of physiotherapy intervention compared with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
183
0
31

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(229 citation statements)
references
References 96 publications
15
183
0
31
Order By: Relevance
“…9,73 In our study, quality of life improved across all groups, although the largest improvement was in the class. Reportedly, quality of life is correlated with depression and apathy, both which improved in the individual therapy group as well.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…9,73 In our study, quality of life improved across all groups, although the largest improvement was in the class. Reportedly, quality of life is correlated with depression and apathy, both which improved in the individual therapy group as well.…”
Section: Discussionmentioning
confidence: 46%
“…14 A recent meta-analysis examined differences between types of exercise by sub-grouping studies according to intervention and found no difference but caution readers about the limited number of studies and the indirect comparison of interventions. 9 …”
Section: Introductionmentioning
confidence: 99%
“…17, 21 A recent Cochrane review reported on the short term effects of physical therapy in PD and concluded that physical therapy utilizing various exercise types can provide small but important changes in walking speed, balance, and clinician rated disability measured by the Unified Parkinson’s Disease Rating Scale (UPDRS). 22 One limitation noted by the review however was that the trials included were relatively small, usually comparing physical therapy to no physical therapy over short periods of time. It is not clear if exercise over long periods conveys continued improvements in patient function or whether the progressive nature of the disease overtakes the benefits of exercise in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…5 Similarly, a recent systematic review of physiotherapy interventions encompassing general physiotherapy, exercise, treadmill training, cueing, dance, and martial arts found that physiotherapy improved mobility but not function over the short term (less than three months). 6 In contrast to these short term changes, van Nimwegen and colleagues' study demonstrated engagement in the exercise programme over two years. Their intervention had several key elements.…”
mentioning
confidence: 89%